Effect of dietary protein supplementation on the resistance of lambs to artificial infection with haemonchus contortus - preliminary results - Haile, Aynalem; Tembely, S.; Baker, R.L.; Anindo, D.O.; Mukasa-Mugerwa, E.; Rege, J.E.O.; Yami, A. (Ethiopian Society of Animal Production, 1998)
The effect of dietary protein supplementation on the resistance of lambs to endoparasites was examined in Horro and Menz lambs artificially infected with Haemonchus contortus. The experimental design involved 2 breeds, 2 infection treatments (infected Vs non-infected) and 3 nutrition treatments. A total of 152 lambs were assigned to 12 treatment combinations, with an average of about 13 animals per cell. Diets were formulated to be isocaloric, but with varying protein and/or nitrogen sources. The nutritional control group of lambs were maintained on a basal diet of hay offered ad libitum, while the second and third nutrition treatments consisted, in addition to the basal diet, of supplements of cotton seed cake (165 g head-1 day-1) and urea molasses blocks (150 g head-1 day-1), respectively. At four months of age, the `infected' group of lambs were exposed to an experimental infection of 1000 L3 (third stage larvae) given orally 3 times a week for 3 weeks. Faecal egg output was monitored 3 times a week starting 3 weeks after the first dose. Packed cell volume and body weight changes were recorded weekly. During the course of the study, infected lambs gained less weight and had lower packed red cell volumes (higher levels of anaemia) (p<0.01) than those non-infected counterparts. Control lambs (infected but kept on the basal diet) gained less weight and had lower packed red cell volumes than supplemented (infected) lambs (p<0.01). The mean faecal egg counts, at the end of the experiment, of lambs on supplemented diet were lower (though not statistically significant, p>0.05) than that of lambs on the basal diet. It was concluded that improved dietary protein supplementation either from CSC or UMB would substantially reduce production losses attributable to infection with contortus.